ASSESSING POTENTIAL ENERGY SUSTAINABILITY OF MICRO-HYDROPOWER SYSTEM THROUGH A SUSTAINABLE INDICATOR APPROACH - Safitri, Icmi Alif; Sulaiman, Muhammad; Budiarto, Rachmawan (Journal of Environmental Science and Sustainable Development, 2024)
The development of micro-scale renewable energy power generation systems, such as micro-hydropower (MHP), often needs more consideration for sustainability during the planning stages. Many small-scale renewable energy systems have shorter-than-expected lifespans, jeopardizing Indonesia's Net Zero Emission Target for 2060 or earlier. Despite this, only some studies have examined the long-term viability of installed renewable energy generation projects, particularly MHP plants not managed by state-owned companies or PLN (Pembangkit Listrik Negara). The primary objectives of this research are to evaluate the feasibility of retrofitting and assess the potential sustainability of a decommissioned MHP in Banjarnegara, Central Java. A cash flow analysis was performed to assess techno-economic indicators. Additionally, the social-institutional dimension was analyzed through in-depth interviews with 15 stakeholders. Sustainability was evaluated using a framework of 15 indicators across technical, economic, environmental, social, and institutional dimensions. The findings revealed that among the four sustainability aspects, the social-institutional dimension scored the lowest potential sustainability at 26.67%. In contrast, the technical and environmental dimensions showed higher potential sustainability, scoring 83.7% and 87.5%, respectively. The economic dimension was deemed feasible only when the financing model accounted solely for retrofitting costs. It is crucial to consider all dimensions comprehensively. Furthermore, engaging multiple stakeholders and fostering local community awareness is vital to ensure the long-term sustainability of decentralized energy systems. This study enhances the understanding of the sustainability potential of abandoned decentralized energy systems and explores how reusing abandoned MHP facilities can support stakeholders in revitalization efforts, contributing to an increased share of renewable energy in the overall energy mix.